(3TQM GdSfIs - (3CHh eMeO GdMSjf Hf eSYhO GdaQGA GdHZhis; (3GdHZhj , GdMSjf Hf eSYhO Hf eMeO GdaQGA, eMjj GdSfI CHh eMeO,J (B510 (3g` s ((3Ydi Hf EHQGgje Hf OGTe Hf CMeO Hf jhSa GdJHQjRi s)
(3ChdgG (B:s
(3cJGH GdLeYI , HGH aQV bGd Gddg JYGdi (B: (3jG CjgG GdPjf BefhG EPG fhOi ddUdGI ef jhe GdLeYI s
(3BNQgG (B:s
(3BNQg ef HGH NQGH GdcYHI ai BNQ GdReGf bhdg (B( (3hGdCaL GdHYjO eG Hjf GdQLdjf hPdc ef fYhJ GdMHTGf BNQ GdeLdO GdKGfi hGdMeO ddg s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdMOjK h GdeUWdMs